Exploring the General Knowledge of Islamic Finance Principles: A Factor Analysis Study Among College Students - Lelis, Christhoffer; Muega, Neil Patrick S.; Caballero II, Jose Karlo T. (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study explored the foundational constructs of general knowledge concerning the principles of Islamic Finance, with a specific focus on college students majoring in Business, Finance, and Accountancy. Employing a combination of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), the research identified and validated three distinct factors shaping this knowledge domain. The first factor, named